Patient Safety Goals’ Level of Attainment in Selected Tertiary Hospitals in Manila, Philippines: A Preliminary Study - Abe, Kenji Hennessy C; Tuppal, Cyruz P (Nurse Media Journal of Nursing, 2018)
Background: Continuous efforts in the implementation of the National Patient Safety Goals (PSG) as a framework to guide the service providers have been made. However,there are reported incidents of untoward patient outcomes due to wrong medication administration, wrong site of surgical operation, acquisition of healthcare-associated infections, adverse reactions, and incidence of fall.Purpose: This study aimed to evaluate the PSGs’ level of attainment in selected tertiary hospitals in Metro Manila, Philippines. Methods: This study employed a field, descriptive and historical research survey conducted in three tertiary hospitals in Metro Manila. The participants were nurses having at least one year of experience in their current workplace (n=214). The sets of questionnaires used to get the data include the demographic profile and PSGs indicators adapted from the National Patient Safety Goals (NPSGs). Data responses were analyzed with descriptive statistics and One-Way ANOVA. Results: Based on the findings, the PSGs level of attainment obtained high extent with overall mean average: PSG 1 (M=4.35), PSG 2 (M=3.97), PSG 3 (M=4.07), PSG 4 (M=3.61), PSG 5 (M=3.89), PSG 6 (M=3.77) and PSG7 (M=4.20). Furthermore, there were significant differences on PSG 3 and PSG 4 with p-values of 0.00 and 0.02 respectively, which were tested at 0.05 level of significance. Others PSGs showed no significant differences. Conclusion: The results indicate that the selected hospitals in Metropolitan Manila, Philippines have a high level of attainment for patient safety goals and remains at the core of health service delivery in each organization. It is recommended that the hospital further enhance the knowledge, skills, and attitudes towards a sustained patient safety culture through continuing education programs, benchmarking, institutionalization, and accreditation.